A high-resolution refractory black carbon (rBC) record since 1932 deduced from the Chongce ice core, Tibetan plateau. (1st February 2023) - Liu, Ke; Wang, Chaomin; Hou, Shugui; Wu, Shuang-Ye; Pang, Hongxi; Zhang, Wangbin; Wang, Yetang; Schwikowski, Margit; Jenk, Theo M.; Zou, Xiang; Yu, Jinhai; An, Chunlei; et al.
Abstract: Refractory Black carbon (rBC) emitted from the combustion of biomass and fossil fuels plays an important role in the climate system. In this study, we established a record of the rBC concentration spanning 1932–2013 from an ice core retrieved from the Chongce ice cap of the West Kunlun Mountains in the western Tibetan Plateau. The record showed an increasing trend since the 1980s. The mean concentration of rBC was 2.66 ng g −1 before 1980 and 5.33 ng g −1 since 1980. The significant increase since the 1980s was very different from similar records from European ice cores. An analysis of atmospheric circulation and backward trajectories suggested that former USSR, the Middle East, and South Asia were the most likely source regions for the rBC deposited at the Chongce ice cap. This conclusion was also supported by the historical emission data in these regions. Phase analysis indicated that high rBC concentrations were closely associated with drought-induced biomass burning in the rBC source regions at the decadal timescale. These findings suggested that anthropogenic emissions controlled the long-term rBC trend, while the peak phases were caused from an increase of biomass burning. Highlights: Anthropogenic activity and climate change play a critical role in the rBC variations over the northwestern Tibetan Plateau. Anthropogenic emissions since 1960s contributed more to rBC deposition. Droughts-induced biomass burning were responsible for high rBC concentration phases.